2010
DOI: 10.1002/jmv.21963
|View full text |Cite
|
Sign up to set email alerts
|

Another novel subgenotype of hepatitis B virus genotype C from papuans of Highland origin

Abstract: Hepatitis B virus (HBV) genotypes and subtypes have been identified worldwide. As HBV genotypes/subtypes, the HBV subgenotypes seem to be associated with their geographical distribution and ethnic origin. A previous study showed the novel HBV subgenotype C6 based on the complete genome sequences of isolates in Papua, Indonesia. In the present study, further characterization of HBV in Jayapura (capital of Papua Province), particularly from native people of Papua originating from the highland (highland Papuans) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Our previous report revealed that >90z of samples obtained from the general population, chronic liver disease patients, and patients on maintenance hemodialysis in Surabaya belong to the genotype B and subtype adw (13); this finding is similar to the results found in other parts of Java Island (10,25), and the genotype/ subtype C/adrq + was mostly found in the most eastern region of Indonesia (in the Papuan ethnic group) (9,25,28). This study showed at least 30z of the samples (3/9) were of C/adrq + , and 2 of them were from Maduranese individuals.…”
supporting
confidence: 76%
“…Our previous report revealed that >90z of samples obtained from the general population, chronic liver disease patients, and patients on maintenance hemodialysis in Surabaya belong to the genotype B and subtype adw (13); this finding is similar to the results found in other parts of Java Island (10,25), and the genotype/ subtype C/adrq + was mostly found in the most eastern region of Indonesia (in the Papuan ethnic group) (9,25,28). This study showed at least 30z of the samples (3/9) were of C/adrq + , and 2 of them were from Maduranese individuals.…”
supporting
confidence: 76%
“…18 Genotype C mainly originated from Far East Asia, Australia, New Zealand, and Polynesia, and it was predominant in eastern Indonesia, including North Sulawesi, Moluccas, and Papua. 13,15,16 Both areas in southeast Sulawesi and West Timor showed a mixed pattern of HBV subtypes. On the other hand, there was an altered pattern of the main subtype in West Papua, from adr to both adr and adw subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Nine HBV genotypes, from A to H and J, that are based on its surface gene, have been documented, [9][10][11][12] and HBV genotypes B and C were predominant among Indonesian populations. [13][14][15][16] Ten HBV serological subtypes, which are based on the amino acid sequences of HBsAg, have been identified. [17][18][19] Indonesia has been geographically divided into four different HBV subtype zones: the adw, adr, ayw, and mix zones.…”
Section: Introductionmentioning
confidence: 99%
“…Norder et al (2004) Mangold et al (1995), revealed that all HBV isolates obtained from HBsAg-positive HBV carriers, including healthy blood donors, patients with acute hepatitis, chronic hepatitis, liver cirrhosis and hepatocellular carcinoma; and patients on hemodialysis all located in Surabaya belonged to genotype B with more than 90% of them being classified into subtype adw. Another survey in Yogyakarta was found (11%), compound subtypes, such as adyw and adyr were detected in the remaining seven (15%) (Juniastuti et al, 2011). HBsAg is a cysteine-rich, lipid-bound protein with 226 amino acids (Zhao et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…B genotype is mostly present in Indonesian ethnic populations and their distribution following the ethno linguistics structure of the population suggest that unlikely that these sub-genotypes have been introduced in recent time. In the subgenotype level, from 440 HBV isolates in Indonesia, B3 is the major sub-genotype (Juniastuti et al, 2011). The combination of amino acid residues in position 122 (d/y) and 160 (w/r) which flank the 'A' determinant provide four major subtypes of HBsAg: adw, adr, ayr and ayw.…”
Section: Introductionmentioning
confidence: 99%